Urinary Microvesicle-Bound Uromodulin: A Potential Molecular Biomarker in Diabetic Kidney Disease - Neng-jun Lou; Yi-hong Ni; Hong-ying Jia; Jing-ti Deng; Lu Jiang; Feng-jie Zheng; Ai-li Sun (Journal of Diabetes Research)
This study was designed to investigate the changes of urinary microvesicle-bound uromodulin and total urinary uromodulin levels in human urine and the correlations with the severity of diabetic kidney disease (DKD). 31 healthy subjects without diabetes and 100 patients with type 2 diabetes mellitus (T2DM) were included in this study. The patients with T2DM were divided into three groups based on the urinary albumin/creatinine ratio (UACR): normoalbuminuria group (DM, n=46); microalbuminuria group (DN1, n=32); and macroalbuminuria group (DN2, n=22). We use a specific monoclonal antibody AD-1 to capture the urinary microvesicles. Urinary microvesicle-bound uromodulin and total urinary uromodulin levels were determined by enzyme-linked immunosorbent assay (ELISA). Our results showed that the levels of urinary microvesicle-bound uromodulin in DN1 and DN2 groups were significantly higher than those in control group and DM group (P<0.01). Multiple stepwise linear regression analysis showed that UACR was independent determinant for urinary microvesicle-bound uromodulin (P<0.05) but not for total urinary uromodulin. These findings suggest that the levels of urinary microvesicle-bound uromodulin are associated with the severity of DKD. The uromodulin in urinary microvesicles may be a specific marker of DKD and potentially may be used to predict the onset and/or monitor the progression of DKD.